Alcinous’ speaking name in the Odyssey: The king of a strong mind (Cadernos de Letras da UFF, 2019)
In this article I contend that the name of Alcinous, the king of the Phaeacians in the Odyssey, is comprised of the terms alkí, ‘strength”, and nóos, ‘mind”, and that Homer makes use of his designation as a characterizing device: a speaking name. To argue so, I carry out a comparative analysis to words with similar formation, and assess how the king’s appearance in the poem contributes to this understanding.---------------------------------------------------------------------------------------------O NOME CARACTERIZANTE DE ALCÍNOO NA ODISSEIA: O REI DE MENTE FORTENeste artigo, defendo que o nome de Alcínoo, o rei dos feácios na Odisseia, seja composto por uma justaposição entre os termos alkí, ‘forca”, e nóos, ‘mente”. Argumento, ainda, que Homero faz uso dessa designação como um elemento de caracterização, um ‘nome caracterizante” (speaking name). Para tal, conduzo uma análise comparativa de palavras com formação semelhante, bem como uma avaliação da atuação do rei no poema.---Original em inglês.